Pendidikan Akhlak sebagai Inti Konsep Pendidikan Islam dalam Pemikiran Al-Ghazali: Penelitian - Ashri Hidayati; Purwoko; Helmawati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Moral education is the core of the Islamic education system, which cannot be separated from scientific, spiritual, and social aspects. This article examines the contribution of Imam Al-Ghazali's thoughts in shaping a value-based Islamic education system and explores the challenges and opportunities for its implementation in the contemporary era. This study employs a qualitative method with a literature review approach, focusing on Al-Ghazali’s major works such as Ihya’ ‘Ulumuddin and Ayyuha al-Walad, as well as secondary literature from various related studies. The main findings indicate that Al-Ghazali places moral education as the foundation of the entire educational process, with tazkiyatun nafs as the central goal. He integrates knowledge and morality into a complementary value system and emphasizes the importance of the teacher’s role as a moral model. However, the implementation of this concept faces various obstacles, ranging from the dominance of cognitive curricula to the lack of spiritual guidance for educators. On the other hand, there are significant opportunities through the integration of values into the curriculum, the use of technology to strengthen character education, and collaboration with the community. This article recommends the renewal of Islamic education policies oriented toward values and spirituality as a response to the current moral crisis.